Production and characterization of monoclonal antibodies against α-globin chain-containing human hemoglobins for detecting α-thalassemia disease. Issue 6 (1st November 2016) - Pakdeepak, Kanet; Pata, Supansa; Chiampanichayakul, Sawitree; Kasinrerk, Watchara; Tatu, Thanusak
ABSTRACT: Monoclonal antibodies against α-globin containing human Hbs, named AMS-Alpha1 and AMS-Alpha 2, were produced by the hybridoma technique using spleen cells enriched by the newly developed B lymphocyte enrichment protocol. These two monoclonal antibodies were of IgM class, reacting to only intact form of human Hbs A, A2, E, and F, which contain α-globin chain. By the indirect ELISA, the AMS-Alpha1 and AMS-Alpha 2 quantified less amount of α-globin chain containing hemoglobins in HbH disease than the SEA-α thalassemia 1 carriers and normal individuals. It was thus anticipated that these monoclonal antibodies can be used for detecting Hb Bart's hydrops fetalis in which no α-globin chain is produced.